2014
DOI: 10.1021/nl500361u
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Catalyzed Electroless Etching of Silicon in Aerated HF/H2O Vapor for Facile Fabrication of Silicon Nanostructures

Abstract: Inspired by metal corrosion in air, we demonstrate that metal-catalyzed electroless etching (MCEE) of silicon can be performed simply in aerated HF/H2O vapor for facile fabrication of three-dimensional silicon nanostructures such as silicon nanowires (SiNW) arrays. Compared to MCEE commonly performed in aqueous HF solution, the present pseudo gas phase etching offers exceptional simplicity, flexibility, environmental friendliness, and scalability for the fabrication of three-dimensional silicon nanostructures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 44 publications
1
52
0
Order By: Relevance
“…We integrated W 2 C/MWNT with p-type Si nanowires and studied their performance for photoelectrochemical (PEC) hydrogen evolution. P-type Si nanowires having an average length of 500 nm were prepared from the Ag-assisted etching of Si wafer (see details in Methods) 42 43 . W 2 C/MWNT was directly dropcast onto these nanowires.…”
Section: Resultsmentioning
confidence: 99%
“…We integrated W 2 C/MWNT with p-type Si nanowires and studied their performance for photoelectrochemical (PEC) hydrogen evolution. P-type Si nanowires having an average length of 500 nm were prepared from the Ag-assisted etching of Si wafer (see details in Methods) 42 43 . W 2 C/MWNT was directly dropcast onto these nanowires.…”
Section: Resultsmentioning
confidence: 99%
“…1D semiconductor nanowires have been widely studied for over two decades for their novel physical and chemical properties and a vast range of potential applications in electronics, piezoelectrics, photovoltaics, mechanics, and sensors . With numerous research efforts devoted, tremendous progress has been made in the controlled synthesis of 1D semiconductor nanowires, including the control of diameter, length, composition, structure and orientation . Among all methodologies developed so far, the vapor–liquid–solid (VLS) process, first proposed by Wagner and Ellis for large whisker growth, has emerged as the most successful and widely adopted method for growing 1D semiconductor nanowires due to its great flexibility and high controllability.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, two independent papers 8,9 demonstrated that a MacEtch reaction could occur by evaporating and condensing the electrolyte on the surface of a metal patterned silicon. Hu et al 8 demonstrated that the MacEtch reaction occurs at room temperature in the presence of aerated HF in a similar fashion of metal corrosion by air.…”
mentioning
confidence: 99%
“…In 2014, two independent papers 8,9 demonstrated that a MacEtch reaction could occur by evaporating and condensing the electrolyte on the surface of a metal patterned silicon. Hu et al 8 demonstrated that the MacEtch reaction occurs at room temperature in the presence of aerated HF in a similar fashion of metal corrosion by air. The oxygen diffusion through the condensed HF/water layer limits the etching rate and the maximum etched depth, so a maximum depth of 6 mm was etched in 3 h. According to Hildreth et al, 9 the electrolyte is evaporated from a liquid solution containing HF and H 2 O 2 and forms a condensed thin layer where the MacEtch reaction occurs.…”
mentioning
confidence: 99%